ANALISIS PENGARUH BIAYA BUNGA, BIAYA KEAGENAN, RISIKO BISNIS,UKURAN PERUSAHAAN, TERHADAP KEBIJAKAN UTANG DAN KEMAMPULABAAN PERUSAHAAN JASA DI BURSA EFEK INDONESIA - Yulinartati, Yulinartati (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2011)
Purpose of this research is to test influence cost of interest, agency cost, business risk, company size to debt directly and indirect of service firm in Indonesian Stock Exchange and test influence of capital sructure influential to profitability of service firm in Indonesian Stock Exchange. This research is including explanatory research explaining the relation of causal between independent variables to variable dependen. Population applied in this research is service firm which listed in Indonesian Stock Exchange (BEI) time line 2006 up to 2008. Data analytical method applied by data normality test and SEM. Result of this research indicates that cost of interest, agency cost, businnes risk and company size influential signifikan to policy of service firm debt in Indonesian Stock Exchange. Cost of interest, agency cost, business risk, company size influential signifikan directly and indirect to profitability of service firm in Indonesian Stock Exchange. Policy of debt influential signifikan to profitability of service firm in Indonesian Stock Exchange. Conclusion from this research is influence cost of interest, agency cost, business risk, company size to policy of debt either directly and also indirect is signifikan at service firm in Indonesian Stock Exchange. Key Word: cost of interest, agency cost, business risk, company size, debt directly and profitability